Marketing certified wood products to Malaysian consumers: exploring issues for the local wood-based industry. - Mohamed, Shukri (Faculty of Forestry, Universiti Putra Malaysia, 2008)
The Malaysian domestic market has yet to be an outlet for certified wood products. Some issues are identified and discussed with the objective of stimulating interest and discussion in marketing of certified wood products to the Malaysian consumers. These are promoting and developing ecologically conscious consumption among the Malaysian public, determining willingness to pay for certified wood products by the consumers and "greening" of the wood products supply chain. The Malaysian consumers could be a market for certified wood products if these issues, and probably many others, are addressed by the country's wood-product manufacturing sector.